Doping, risk and abuse: An interview study of elite athletes with a history of steroid use - Hoff, D. (Performance Enhancement & Health, 2012)
Risk behaviour such as the abuse of alcohol and drugs has been associated with doping in sport. This article investigates doping use in relation to substance abuse, health risks, risks of being caught in a doping control, and other risk behaviours, in a qualitative interview study of 11 Swedish elite athletes sanctioned for using anabolic androgenic steroids (AAS) during their sports careers. The interviews show that most respondents have not experienced any serious negative side effects due to AAS use, and report several positive effects. The respondents were using moderate doses to avoid health risks, and their use was characterised by conscious risk management to avoid being caught in doping control. Most respondents were not abusing other substances than AAS, and did not perceive themselves as risk-takers. The results point to the possibility that doping use in sport needs to be studied by methods and perspectives other than as abusive and/or health risk behaviour. Instead, the internal logic of sport and sport specified norms have to be visualised and analysed to understand doping phenomena.